2012
DOI: 10.1029/2011jb008842
|View full text |Cite
|
Sign up to set email alerts
|

Serpentinization of oceanic peridotites: 2. Kinetics and processes of San Carlos olivine hydrothermal alteration

Abstract: [1] The kinetics of the reaction (Mg,Fe)-olivine + H 2 O → serpentine + magnetite + brucite + H 2 were investigated at 500 bars in the 250-350 C range using natural olivine (San Carlos; Fo 91 ) with grain sizes between 1 and 150 mm and for run durations up to 514 d. The amount of magnetite produced, which directly relates to reaction progress, was accurately monitored using up to 24 time-resolved magnetic measurements per experiment. Eighty percent of serpentinization was achieved after 60 d for olivine grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
192
2
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(206 citation statements)
references
References 68 publications
11
192
2
1
Order By: Relevance
“…These experiments were performed using methods very similar to those of this study, except that the reaction vessel was periodically rotated during heating. After heating for [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] (Table 1). However, isotopic labeling indicated that the CH 4 in our experiments was not derived from reduction of dissolved inorganic carbon but instead, was derived entirely from background sources (i.e., composed of 99 mol % 12 CH 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These experiments were performed using methods very similar to those of this study, except that the reaction vessel was periodically rotated during heating. After heating for [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] (Table 1). However, isotopic labeling indicated that the CH 4 in our experiments was not derived from reduction of dissolved inorganic carbon but instead, was derived entirely from background sources (i.e., composed of 99 mol % 12 CH 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The experiments were conducted over a temperature range of 200°C to 320°C. Experiments were not extended to lower temperatures, because the rates of serpentinization were found to be too slow below 200°C to be readily observable on laboratory timescales (29,30).…”
mentioning
confidence: 99%
“…Without fracturing in concert with carbonation, the solid volume increase and pore filling processes associated with these reactions would decrease flow rates and thus the rate of carbon sequestration. As argued by Kelemen et al (2011), there is every reason to believe that carbonate growth in partly serpentinised peridotites near the surface in Oman would be able to drive fracturing by a mechanism similar to the serpentinisation driven fracturing first proposed by MacDonald and Fyfe (1985) and confirmed by many subsequent studies, including the recent experiments of Malvoisin et al (2012).…”
Section: Implications For Large Scale Co 2 Sequestrationmentioning
confidence: 76%
“…Interestingly, the experiments of Malvosin et al (2012) show the same sigmoidal shape predicted by our model. Fracturing of olivine grains is also observed in the serpentinisation experiments and Malvoisin et al (2012) stressed the role of new surface area production by etch pit formation and fracturing. The causal connection between these two processes was proposed by Plümper et al (2012;Fig.…”
Section: Reaction Progress Versus Timementioning
confidence: 80%
See 1 more Smart Citation